A STUDY OF BIOCHEMICAL CHANGES IN THE TISSUES OF ZEBRAFISH (DANIO RERIO) ON EXPOSURE TO ORGANOPHOSPHORUS PESTICIDES - Abeer Ghazie A. Al Safi (Basrah Journal of Veterinary Research)
The aim of this study was to investigate the acute toxicity of Organophosphate(Malathion and Atrazine), and determined the accumulation of these pesticides in thewhole body of zebrafish, and some biochemical responses in its brain and muscle.The results showed that MAL and ATR could be rapidly accumulated in the fish bodyshortly after being exposed to acute concentrations of the toxicants and exhibited adose-dependent manner. This was also validated by the response of antioxidantdefense, superoxide dismutase and catalase, both exhibited significant increase inactivity. Acetylcholinesterase activity of zebrafish was also shown inhibited in adose-dependent manner.